PERAN UNITED NATIONS CHILDREN'S FUND (UNICEF) DALAM MENANGGULANGI MASALAH PERNIKAHAN ANAK DI INDONESIA PERIODE 2014-2017 - Herviryandha, - (2018)
This thesis discusses the role of the United Nations Children's Fund (UNICEF) in Tackling Child. Marriage Problems in Indonesia Period 2014-2017. One of the major problems faced by Indonesia is the issue of child marriage is still rampant in Indonesia. UNICEF is one of the international organizations engaged in protecting children and women around the world. How UNICEF's role in tackling the problem of child marriage in Indonesia has been raised as a matter of research. The concepts of the International Organization, Role Theory and Child Marriage are used in this issue. To tackle the problem of child marriage in Indonesia, UNICEF conducted a cooperation program with the Government of Indonesia which is expected to reduce child marriage so that children in Indonesia get their rights well. In carrying out its role in Indonesia, UNICEF is an international organization that has a role as an instrument, UNICEF provides support and motivation to the Government of Indonesia to help tackle child marriages with the goal that all children in Indonesia, both men and women, can get their rights from education, health and protection